Until the end of time [compact disc, unabridged] : mind, matter, and our search for meaning in an evolving universe - Greene, B. (Brian), 1963- (Random House Audio, 2020)
The Columbia University theoretical physicist and best-selling author of The Elegant Universe explores subjects ranging from quantum mechanics to black holes, sharing insights into how human life and consciousness emerged from chaos.